How Much Can Financial Literacy Help? - Guiso, Luigi; Viviano, Eliana (Review of Finance, 2015)
We use a dataset of individual investors containing test-based measures of financial literacy and administrative records on their assets holding and trades before and during the financial crisis of September 2008. We design three tests of the benefits of financial literacy during the Global Financial Crisis, by comparing the decisions actually taken by individuals with a dominated alternative, i.e., one giving lower utility according to simple normative models of financial decision-making. We find that high-literacy investors are better at timing the market. High-literacy investors are also more likely to trade according to the prescriptions of normative models and to detect intermediaries’ potential conflicts of interest. However, though statistically significant, these effects are economically small.